Hambatan Komunikasi dan Adaptasi Budaya Mahasiswa Bengkulu di Lingkungan Minangkabau - Amelia Rahmi; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the communication barriers and cultural adaptation of students from Bengkulu in the Minangkabau environment. The research employs a qualitative approach with interview methods involving a research subject, RM, a 19-year-old student from Bengkulu studying at UIN Syech M. Djamil Djambek Bukittinggi. Data were collected through in-depth interviews and analyzed to identify patterns of communication barriers and the adaptation process experienced by the subject. The intervention applied used the Social Skills Training technique to enhance the subject’s intercultural communication competence. The findings indicate that the communication and adaptation barriers experienced by RM stem from differences in the system of linguistic norms and communication culture between regions. Lack of awareness regarding the hierarchy of language politeness and social etiquette in Minangkabau led to miscommunication, which resulted in social anxiety, reduced interaction intensity, and diminished client self-confidence. The adaptation process experienced by RM suggests that culture is dynamic and can be internalized through social contact, field experience, and responsive environmental support. Thus, culturally informed counseling assistance becomes a decisive factor in facilitating the client’s adjustment to local communication norms without sacrificing their original cultural identity. Based on the analysis, the effectiveness of cross-cultural counseling is determined by the counselor’s cultural awareness, orientation toward diversity as a resource for personal development, and the selection of intervention strategies aligned with the client’s sociocultural context. The integration of the Person-Centered Approach and Social Skills Training demonstrates empirical relevance in helping RM create a psychologically safe space for self-expression while strengthening communicative competence in accordance with Minangkabau norms. These findings confirm that cultural adaptation can proceed optimally when accompanied by professional support that is supportive, educational, and reflective.